Menstruation and the menstrual cycle in sport, exercise and physical activity (Routledge, 2026)
Menstruation and the Menstrual Cycle in Sport, Exercise, and Physical Activity is the first book to offer students, researchers, and professionals an evidenced-based reference on considerations and concepts relevant to sports performance and physical activity during menstruation and the menstrual cycle, showcasing multidisciplinary perspectives in subdisciplines of sport and exercise science, including physiology, psychology and biomechanics, and social science. This new book presents research insights and theoretical underpinnings as it explores targeted interventions to support sport, exercise, and physical activity engagement throughout the menstrual cycle. Bringing together internationally leading researchers to present a range of research and practice issues connected to menstruation and the menstrual cycle in various physical activity environments, Menstruation and the Menstrual Cycle in Sport, Exercise, and Physical Activity examines key topics such as the impact of menstruation on sport training and performance, menstrual health literacy in sport, menstrual health monitoring, and menstrual stigma. Menstruation and the Menstrual Cycle in Sport, Exercise, and Physical Activity is key reading for researchers, undergraduate and postgraduate students, practitioners, and coaches working with menstruators in sport, exercise, and physical activity settings, providing a useful resource for inquiry, discussion, and learning about menstruation and the menstrual cycle in sport, exercise, and physical activity. Table of contents: